(untitled) (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2024)
Teaching folk songs in the aesthetic education of students fosters cultural awareness, emotional intelligence, and artistic development. This article explores key pedagogical conditions necessary for effective instruction, including creating a supportive environment, contextualizing songs, employing active and creative methods, integrating technology, and ensuring teacher preparedness. Community engagement and interdisciplinary approaches further enhance the learning experience. Despite challenges such as diminishing interest and limited resources, innovative strategies can revitalize the role of folk songs in education. The findings emphasize their significance in nurturing students’ holistic growth and sustaining cultural heritage through aesthetic learning.